(untitled) (Asian Journal of Agriculture, 2022)
Abstract. Gabriel MG, Alhasan U, Mary Y, Munsur Y, Olufunmilayo A. 2022. Screening of rice germplasm for blast resistance in Nigeria. Asian J Agric 6: 1-6. Rice blast (Magnaporthe oryzae T.T. Hebert) M.E. Barr) is an important destructive disease of rice that can lead to 80% yield loss. Germplasm responds differently to blast fungus. This study aimed to screen rice germplasm for blast resistance in Nigeria. The four genotypes, namely Institute for Research in Tropical Agriculture, France (IRAT) 109, JAMILA, Federal Agriculture Research Oryza (FARO) 52, and FARO 66, were evaluated in a completely randomized design with three replications in the screen house of the Department of Crop Protection, Institute for Agricultural Research Samaru, Nigeria. Data were collected on plant height, the number of plants infected with a blast, seedling vigor, tillering ability, blast disease score, and leaf blast estimated. Analysis of variance showed a highly significant difference (P ? 0.01) for seedling vigor (0.03**) and disease index (17.24**), while significant (P ? 0.05) variation was observed for a number of the leaf (3.79*). In contrast, there was no significant (P > 0.05) variation for plant height and tillering ability. The highest PCV (Phenotypic Coefficient of Variance) and GCV (Genotypic Coefficient of Variance), also broad-sense heritability, were observed in leaf blasts. IRAT 109 (0.6) depicted a high resistance, JAMILA moderately susceptible (Blast score 4.0), while FARO 52 (7.3) and FARO 66 (6.1) were susceptible. A significant difference among genotypes implies sufficient variation among the genotype screened, suggesting that progress can be made following selection.